Toxicological Profile of Pomegranate (Punica Granatum) Peel Extract and Histopathological Assessment in Zebrafish (Danio rerio): An In-Vivo Study - Agarwal, Renu; Shobana , Chandrasekar; Rohini, Durairaj; Usharani, Boopathy; V, Suganthi (International Journal of Membrane Science and Technology, 2023)
Background: Fruit – by - product includes peels, seeds, leaves, residual pulp, stems and discarded pieces from a variety of sources. Pomegranate (Punica granatum) peel is a good source of bioactive compounds, antioxidants, nutraceuticals, and functional properties and there is a healthy trend towards by-product utilization and value addition. However, its toxicity and its adverse effects were not intensively studied. Objective: This study aimed to examine the In-vivo toxicity of Pomegranate Peel Powder (PPP) extract and histopathological assessment using zebrafish (Danio rerio). Methods: Decoction (Aqueous) by Soxhlet method was used for extraction from Pomegranate Peel Powder (PPP). Dense extract was used to study toxicity level and it was assessed using Dose Dependent Toxicity Assessment (DDTA) with Zebrafish. The mature Zebrafish were divided into eight groups (A, B, C, D, E, F, G, and control) based on their average body weight, with eight fishes in each tank. Fish groups (8 fishes/concentration) were treated to different doses and concentrations of Pomegranate Peel Powder (PPP). Fish mortality was monitored and recorded after 24, 48, 72, and 96 hours. After acute toxicity analysis, H & E staining was performed to analyse the zebrafish brain. At least 3 fish from each group were taken and analysed for histopathological scoring. Result: At 24 hr and 96 hr exposure periods, the lethal dosage, to kill 50% of test fishes, was 800 mg/L. Fish treated with 200 mg/L dosage had a score grade of 1 and showed no toxic pathological changes when compared to 400 and 800 mg/L doses because they considerably had decreased pathological scores of neuronal damages, which was equivalent to the control group. Zebrafish treated with 12.5 – 200 mg/L showed no toxic effect in the brain of fish, which was comparable with the control. Conclusion: The current study showed that the No-Observed Adverse Effect Level (NOAEL) is evaluated to be 200 mg/L dosage. Thus, PPP has less toxicity, and its use is suggested with potential applications against diseases.